2014
DOI: 10.1002/ardp.201400084
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Novel 3‐Aryl‐5‐(4‐chloro‐2‐morpholinothiazol‐5‐yl)‐4,5‐dihydro‐1H‐pyrazoles and Their Antifungal Activity Alone and in Combination with Commercial Antifungal Agents

Abstract: The α,β-unsaturated carbonyl compounds 5a-f were prepared by reaction between 2-chloro-4-morpholinothiazol-5-carbaldehyde 3 and substituted acetophenones 4a-f. Treatment of compounds 5a-f with hydrazine hydrate employing mild reaction conditions led to the formation of 4,5-dihydro-1H-pyrazoles 6a-f. Then the treatment with acetic anhydride or formic acid afforded the expected 4,5-dihydro-1H-pyrazoles 7a-f and 8a-f. The antifungal activity of each series of synthesized compounds was determined against the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
1
1
0
1
Order By: Relevance
“…In the current study, ATTAF-1 and ATTAF-2, two promising novel azole compounds, could show potent activity against all Candida species when used alone or in combination with fluconazole. In line with the present results, Shi et al (23) and Ramírez et al (24) showed that the newly synthesized azole-based compounds were more active than fluconazole and the combination of these compounds with fluconazole could exert synergistic effects. Moreover, Ji et al (25) synthesized triazole derivatives based on the structure of lanosterol 14␣-demethylase (CYP51) and revealed that these compounds have better activity against C. albicans than does fluconazole.…”
supporting
confidence: 91%
“…In the current study, ATTAF-1 and ATTAF-2, two promising novel azole compounds, could show potent activity against all Candida species when used alone or in combination with fluconazole. In line with the present results, Shi et al (23) and Ramírez et al (24) showed that the newly synthesized azole-based compounds were more active than fluconazole and the combination of these compounds with fluconazole could exert synergistic effects. Moreover, Ji et al (25) synthesized triazole derivatives based on the structure of lanosterol 14␣-demethylase (CYP51) and revealed that these compounds have better activity against C. albicans than does fluconazole.…”
supporting
confidence: 91%
“…Adicionalmente, los compuestos más activos 42e y 42f fueron probados en combinación con los agentes antifúngicos comerciales: fluconazol, itraconazol y amfotericina B. El compuesto 42e mostró un efecto sinérgico con fluconazol contra C. albicans mientras que 42f mostró actividad sinérgica con todos los fármacos antifún-gicas probadas contra la misma cepa. (Ramírez, et al, 2014 La reacción de ciclocondensación asistida por microondas de las chalconas 17/18 con hidrazina produjo los nuevos 3-aril-4-(3-aril-4,5-dihidro-1H-pirazol-5-il)-1-fenil-1H-pirazoles racémicos 55 o sus N-acetil derivados 56 y 57 cuando las reacciones se llevaron a cabo en DMF o ácido acético, respectivamente ( Figura 15S, http://www.raccefyn. co/index.php/raccefyn/article/downloadSuppFile/309/1485).…”
Section: Síntesis De Pirazolinas a Partir De Chalconasunclassified
“…Based on the above considerations and as a part of our current project devoted to the synthesis of novel nitrogen-containing heterocyclic compounds with biological activity [9,10,11,12,13], we decided to attempt the synthesis of hybrid compounds composed of both the 7-chloro-4-aminoquinoline nucleus and the substituted 2-pyrazoline moiety in a single structure ( 15 – 38 , Scheme 1) looking for compounds with significant biological activities.…”
Section: Introductionmentioning
confidence: 99%